Investigation of prechilling and scarification (chemical and physical) treatments in break of wild mustard (Sinapis arvensis) seed dormancy - حسین رضوانی; جعفر اصغری; سید محمدرضا احتشامی (علوم و فناوری بذر ایران)
To find methods of breaking seed dormancy,an experiment was arranged in a factorial experiment based on a completely randomized design with three replications in laboratory ofGorgan University of Agricultural Sciences and Natural Resourcesduring 2010. The seeds were divided into three portions. Two portions of seeds within a period of two and four weeks in temperature of 4οC was remained uniformity under moist conditions (cold stratification) and one another part of seeds located in laboratory conditions and ordinary temperature. Then nine mechanical and chemical scarification treatments (using of gibberellic acid with concentration of 500, 1500 and 2000 ppm; 1, 2 and 4 minutes soaking in sulfuric acid; 1, 2 and 3 minutes of using of Emery)were applied on these seed portions and the germination percentage, rate and uniformity were investigated. Also, in order to determine the effect of treatments on permeability of seed coat to water, water adsorption trend of wild mustard (Sinapis arvensis) seed was studied after using of treatments. Results of experiment indicated that prechilling, scarification treatments and their interaction effects have significant effect on germination components. According to results, effective treatments following by 24 hours of soaking in gibberllic acid(density=2000, 1500 ppm) andmechanical scarification for 2 minutes treatment, in non-prechilling and 2 weeks prechilling. No use of prechilling treatment, germination percentage in 24 hours of soaking in gibberllic acid(density=2000, 1500 ppm) andmechanical scarification for 2 minutes treatment observed 58.5, 56 and 47.5%, respectively. Despite two weeks of moist chilling, germination percentage of these treatments with a slight increase was about 77.25, 76.5 and 53.25%, respectively, meanwhile under four weeks of moist chilling, germination percentage in above treatments decreased about 77, 65 and 66%. In the end it became clear that the best treatment for reduction of wild mustard seed dormancy and improve its germination was 24 hours of soaking in gibberllic acid(density=1500 ppm) andemery for 2 minutes treatment